Faktor-Faktor yang Berhubungan dengan Kejadian Keputihan Pada Mahasiswi S1 Kebidanan Reguler Universitas Kader Bangsa Palembang Tahun 2021 - Sulistiawaty Sulistiawaty; Fika Minata Wathan; Titin Dewi Sartika Silaban (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
According to the World Health Organization (WHO) reproductive health is a complete physical, mental and social state, not only free from disease or disability in all aspects related to the reproductive system, its function and process Vaginal discharge or flour albus / leukorea is a white liquid that comes out of the intercourse excessively. In Indonesia, 75% of women have experienced vaginal discharge at least once in their lives and half of them have experienced vaginal discharge twice or more. The purpose of this study was to determine the facto-factors related to the incidence of vaginal discharge in regular Midwifery S1 students of the Palembang National Cadre University. This research uses a cross-sectional approach This research was carried out in January-February 2022 at the University of Kader Bangsa Palembang. The population in this study was regular Midwifery S1 students totaling 50 female students. The sample was taken using the total sampling technique of 50 respondents. Based on the chi-square statistical test, it was found that there was a relationship between the physical activity variable and the incidence of vaginal discharge with a p value of 0.000 (OR 28,333), there was a relationship between sleep patterns and the incidence of vaginal discharge with a p value of 0.000 (OR: 17,857), there was a relationship between personal hygiene and the incidence of vaginal discharge with a p value of 0.000 (OR: 20,700). It can be concluded that there is a relationship between physical activity, sleep patterns and personal hygiene with the incidence of vaginal discharge. The results of the study are expected to provide information or add new knowledge in preventing vaginal discharge..